Effectiveness of Community Based Forest Managementas Forest Resources Conflict Resolution - Arifandy, M Imam; Sihaloho, Martua (Sodality: Jurnal Sosiologi Pedesaan, 2015)
Community Based Forest Management (CBFM) is a system of state forest management that conducted Perhutani joinly with community forestry forest villages. CBFM include: drafting plans, utilization of forest resources, and protection of forest resources. CBFM regulated the rights and obligations of all stakeholders involved. Conflict of interest in the management of forest resources can lead to conflicts beetwen any stakeholders. This research aim to determine (1) history and sources of forest resources conflict in the Kalimendong village, (2) conflict resolution mechanism that were implemented based on the CBFM, (3) effectiveness CBFM as conflict resolution in forest resources management. The result of this study found that the conflict in Kalimendong village occured since 1998 that comes from the differences in perception, interest, and ownership beetwen the public and Perhutani. CBFM then can be conflict resolution of forest resources management, but CBFM can then generate a new conflict when the interests of stakeholder can not be accomodated. The analysis shows that characteristic of number of dependents has negatively correlation related to the effectiveness of CBFM as conflict resolution.Keywords: conflict, CBFM, conflict resolution, forest resources